2020
DOI: 10.3738/1982.2278.3743
|View full text |Cite
|
Sign up to set email alerts
|

DIVERSIDADE GENÉTICA DE Desmanthus virgatus L. EM SERGIPE

Abstract: A jureminha (Desmanthus virgatus L.) é uma leguminosa forrageira, nativa do Nordeste brasileiro. Em Sergipe é encontrada na zona da mata, agreste e no semiárido. É rica em proteína, sendo uma alternativa promissora para agropecuária. Os acessos mantidos em bancos de germoplasma são fontes de variabilidade genética para os programas de melhoramento, sendo a caracterização molecular importante ferramenta na identificação de duplicatas e seleção de genótipos. O objetivo do trabalho foi estimar a diversidade genét… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…, 2016), and a study on Vigna unguiculata L. found a mean value of 0.6383 (IGWE et al, 2017). Similar results were found by Queiroz (2016) when using AFLP markers for accessions of Desmanthus sp., with H e of 0.29, denoting low genetic diversity; and by Soares et al (2020), who found H e of 0.25 when using RAPD. These results are probably connected to the species reproduction system, which can affect the genetic diversity among individuals (SOARES et al, 2016) The PCR-ISSR technique enabled the development of a Jaccard similarity matrix, which presented values between 0.50 and 0.97 ( Formation of three groups was observed, considering the similarity of 0.67 (Figure 4).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…, 2016), and a study on Vigna unguiculata L. found a mean value of 0.6383 (IGWE et al, 2017). Similar results were found by Queiroz (2016) when using AFLP markers for accessions of Desmanthus sp., with H e of 0.29, denoting low genetic diversity; and by Soares et al (2020), who found H e of 0.25 when using RAPD. These results are probably connected to the species reproduction system, which can affect the genetic diversity among individuals (SOARES et al, 2016) The PCR-ISSR technique enabled the development of a Jaccard similarity matrix, which presented values between 0.50 and 0.97 ( Formation of three groups was observed, considering the similarity of 0.67 (Figure 4).…”
Section: Resultsmentioning
confidence: 98%
“…The number of fragments was lower than that reported by Costa et al (2017), who used 8 primers and found 95 fragments, resulting in a stress value of approximately zero. Soares et al (2020) used RAPD primers for evaluating the genetic diversity of 242 individuals from three ecogeographic regions of the state of Sergipe, Brazil (Zona da Mata, Agreste, and Semiarid regions), and found 96.33% polymorphism.…”
Section: Resultsmentioning
confidence: 99%